MASJID BAGI WANITA MENTRUASI (HAID) - Syahril, Syahril (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2012)
This research was aimed at explaining the law perspective for women to enter mosque while having menstruation. This study employed library research. Data analysis used descriptive analysis. The findings showed that mosque as a place for worship is considered similar to Ka’bah. Syafi’I prohibits the women to enter mosque and stay inside. However, such interpretation is believed as a product of intellectual interpretation. As a result, as their nature, man can be right or wrong